Lakas Application to Improve Sentence Construction Skills for Deaf Students - Paramuditha, Widi Kumara Jaga; Marlina, Marlina (Department of Special Education, 2024)
This research was motivated by the lack of learning media to construct sentences for deaf students. So the purpose of the research is to develop learning media in the form of the Lakas Application (structured sentence exercises). This study uses a research and development approach method with the ADDIE design. Due to time constraints, researchers carried out the level one research stage consisting of three research steps, namely the analysis-design-development stage. The subjects of this research and development trial were related experts such as deaf student experts, deaf student tool experts and deaf student learning experts. As well as a practicality test by an educator and 2 deaf students. Data collection tools in the form of a questionnaire for the validity instrument of the Lakas Application product and an instrument for assessing the response of the Lakas Application product. The data analysis technique used is a descriptive data analysis technique. The results of this study indicate that the Adobe Flash-based Lakas Application learning media is useful and worthy of being used as a learning medium in the skill of constructing SPOK structured sentences with a validation value of 96% and a practicality test of 89%. The final form of this product is a learning media packaged in the form of an android application so that it can be opened anywhere and anytime via an android smartphone.